2013
DOI: 10.1371/journal.pone.0074217
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of the Processes of Surface Brown Spot (SBS) Formation in Pear Fruit (Pyrus bretschneideri Rehd. cv. Dangshansuli) by De Novo Transcriptome Assembly

Abstract: Browning disorder, which usually occurs post-harvest in pears subjected to long-term storage, can cause browning of the pear flesh and/or core. In 2011, investigators in China found a novel type of brown spot (designated as surface brown spot, SBS) in pre-harvest ‘Dangshansuli’ pears (Pyrus bretschneideri Rehd.). SBS has a large impact on the exterior quality of the pears. Interestingly, the brown coloration was only found on the peel and not the flesh or the core. In this paper, de novo transcriptome analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…To our knowledge, this is the first report to show that photosynthesis genes are associated with explant browning. Liu et al [ 18 ] also confirmed that photosynthesis changes during pear fruit browning. These metabolic processes will disrupt the energy metabolism providing a molecular context for the formation of ROS in browning tissue.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…To our knowledge, this is the first report to show that photosynthesis genes are associated with explant browning. Liu et al [ 18 ] also confirmed that photosynthesis changes during pear fruit browning. These metabolic processes will disrupt the energy metabolism providing a molecular context for the formation of ROS in browning tissue.…”
Section: Discussionmentioning
confidence: 80%
“…The energy-related and stress-related genes were also altered during apple fruit browning development. To investigate pear fruit surface brown (SBS), transcriptome analysis showed that up-regulated the expression of genes related to oxidative phosphorylation, phenolic compound synthesis and PPO [ 18 ]. These studies provide a genomics basis for botanists to understand the molecular mechanisms of enzymatic browning.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little knowledge available at the proteomic level, which would be valuable in understanding the molecular mechanisms of PB development in the ‘Nanguo’ pear. Transcriptomics analyses in pear fruit focusing on the peel brown spots have recently been reported . However, some discrepancies have been found between transcript content analysis and protein content analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomics analyses in pear fruit focusing on the peel brown spots have recently been reported. 5 However, some discrepancies have been found between transcript content analysis and protein content analysis. A more accurate method involves iTRAQ-based technology that can simultaneously label and accurately quantify proteins from multiple samples, 6,7 and it has been used to quantify and characterise changes in protein levels in a wide range of studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies of transcriptomic profiles revealed that the expression of sequences associated with ethylene, abscisic acid and gibberellin metabolism were affected during browning of pear and apple [14,23]. In our transcriptomic analysis, an unigene annotated as IAA-amino acid hydrolase was up-regulated and four unigenes related with auxin efflux carrier were down-regulated in the YLB05 library (Table 3).…”
Section: Discussionmentioning
confidence: 62%